2020
DOI: 10.24871/191201810-15
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Curcumin Against Matrix Metalloproteinase-2 (MMP-2) and Tissue Inhibitor Metalloproteinase-2 (TIMP-2) Serum Level on Rat Model of Liver Fibrosis Resolution Process

Abstract: Background: Liver fibrosis is an effect from continuous fibrogenesis and fibrolysis process. During fibrogenesis, MMP-2 and TIMP-2 that produced by hepatic stellate cell (HSC) have a role to regulate extracellular matrix (ECM) homeostastic. Otherwise, curcumin inhibits both MMP-2 and TIMP-2 expression and enhances HSC apoptosis, thus inhibit fibrogenesis. Role of curcumin, MMP-2, and TIMP-2 in a fibrolysis process has not been widely studied. This study aimed to determine the correlation between curcumin admin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…MMP-13 is responsible for the turnover of major fibrillar collagens in rats and mice. A reduction in MMP-2 activity, ECM deposition, and liver fibrosis was also observed in 9-week CCl 4 -or 7-week TAA-treated male Wistar rats received curcumin treatment for 2 and 7 weeks, respectively (Ali et al, 2014;Supriono et al, 2020).…”
Section: Role Of Phytochemicals In Liver Fibrosis and Ecm Turnover (D...mentioning
confidence: 80%
See 1 more Smart Citation
“…MMP-13 is responsible for the turnover of major fibrillar collagens in rats and mice. A reduction in MMP-2 activity, ECM deposition, and liver fibrosis was also observed in 9-week CCl 4 -or 7-week TAA-treated male Wistar rats received curcumin treatment for 2 and 7 weeks, respectively (Ali et al, 2014;Supriono et al, 2020).…”
Section: Role Of Phytochemicals In Liver Fibrosis and Ecm Turnover (D...mentioning
confidence: 80%
“…MMP‐13 is responsible for the turnover of major fibrillar collagens in rats and mice. A reduction in MMP‐2 activity, ECM deposition, and liver fibrosis was also observed in 9‐week CCl 4 ‐ or 7‐week TAA‐treated male Wistar rats received curcumin treatment for 2 and 7 weeks, respectively (Ali et al, 2014; Supriono et al, 2020). In contrast, Wang et al reported that curcumin significantly increased active MMP‐2 levels in the liver of male SD rats after induction of fibrosis by CCl 4 for 8 weeks (Wang et al, 2018).…”
Section: Role Of Phytochemicals In Liver Fibrosis and Ecm Turnover (D...mentioning
confidence: 95%
“…The ability of curcumin to down-regulate the expression of fibronectin, one of the ECM proteins, which is overexpressed in leiomyoma as compared to normal myometrium, has also been documented ( Malik et al, 2009 ). The significant inhibitory effect of curcumin on the expression of ECM receptors in non-small-cell lung cancer ( Li et al, 2017 ) and reducing the activity of MMP-2 and up-regulating TIMP activity in various cancer cells ( Mitra et al, 2006 ; Hassan and Daghestani, 2012 ; Supriono et al, 2018 ) suggest the possible mechanism of curcumin in producing anti-uterine fibroid activity via reducing the ECM production, thus further study investigating the effects of curcumin on various ECM-related receptors and proteins in leiomyoma cells may be conducted.…”
Section: Botanical Drugs With Anti-uterine Fibroid Activitymentioning
confidence: 99%
“…In patient diagnosis, coronary atheromatous plaque is determined by CT value, and the CT value is expressed by HU. When the CT value is less than 60HU, the patient is a soft plaque; When the CT value is between 60 and 130 HU, the patient is a fibrous plaque; When the CT value is greater than 130HU, the patient is calcified plaque (11,12).…”
Section: Observationsmentioning
confidence: 99%